PENANGANAN PELANGGARAN SERTA PERAN APARATUR SIPIL NEGARA (ASN) SEBAGAI PENCIPTA IKLIM KONDUSIF DEMOKRASI DALAM PENYELENGARAAN PEMILU - Suhendar, Suhendar; Rachmi Kusumah, Riva (Universitas Wiralodra, 2020)
Neutrality is an important capital for the State Civil Apparatus (ASN) as the government organizer. However, it is not easy to realize the principle called neutrality. There are several factors that make it difficult for ASNs to be neutral. First, the massive amount of ASN. ASN has a good understanding of the government's governance policies, as well as the authority possessed by the country's civil apparatus. Various regulations related to elections both in the handling of violations and the state civil apparatus are indeed well structured, but they should be able to reduce the potential behavior of the community, election participants and election organizers, but the potential for violations in the general election yesterday was large enough so that the authors are interested in researching deeper, based on Indonesia being a state of law both the government and its people must obey and abide by existing laws, but unfortunate law made easily by the public is one of the regulations related to general elections, this paper focuses on the role of the state civil apparatus in organizing general elections and handling election violations in the Indramayu district